In‐vitro analysis of early calcification in aortic valvular interstitial cells using Laser‐Induced Breakdown Spectroscopy (LIBS). Issue 1 (9th May 2017) - Davari, Seyyed Ali; Masjedi, Shirin; Ferdous, Zannatul; Mukherjee, Dibyendu
Abstract: Calcific aortic valve disease (CAVD) is a major cardiovascular disorder caused by osteogenic differentiation of valvular interstitial cells (VICs) within aortic valves. Conventional methods like colorimetric assays and histology fail to detect small calcium depositions during in‐vitro VIC cultures. Laser‐induced breakdown spectroscopy (LIBS) is a robust analytical tool used for inorganic materials characterizations, but relatively new to biomedical applications. We employ LIBS, for the first time, for quantitative in‐vitro detection of calcium depositions in VICs at various osteogenic differentiation stages. VICs isolated from porcine aortic valves were cultured in osteogenic media over various days. Colorimetric calcium assays based on arsenazo dye and Von Kossa staining measured the calcium depositions within VICs. Simultaneously, LIBS signatures for Ca I (422.67 nm) atomic emission lines were collected for estimating calcium depositions in lyophilized VIC samples. Our results indicate excellent linear correlation between the calcium assay and our LIBS measurements. Furthermore, unlike the assay results, the LIBS results could resolve calcium signals from cell samples with as early as 2 days of osteogenic culture. Quantitatively, the LIBS measurements establish the limit of detection for calcium content in VICs to be ∼0.17±0.04 μg which indicates a 5‐fold improvement over calcium assay.Picture : Quantitative LIBS enables in‐vitro analysis for early stage detection of calcium deposition within aortic valvular interstitial cells (VICs). Abstract : Quantitative LIBS enables in‐vitro analysis for early stage detection of calcium deposition within aortic valvular interstitial cells (VIC).